Effect of different concentration of rapeseed‐oil‐based polyol and water on structure and mechanical properties of flexible polyurethane foams. Issue 35 (3rd June 2015) - Malewska, Elżbieta; Bąk, Szymon; Prociak, Aleksander
ABSTRACT Flexible polyurethane foams (FPURFs) with varied concentration of water from 3.2 to 4.2% and rapeseed oil based polyol (ROP) in the range of 13–22% in polyol premix were obtained. Effects of changes in polyurethane (PUR) formulation on the foaming process and mechanical properties of FPURFs were analyzed. It was found that the change of water content in PUR formulation influences its foaming process. Higher water content in the PUR formulation increases the growth velocity and the temperature of reaction mixture. In the case of foams modified with ROP, an opposite effect can be observed, where higher content of that component resulted in overall downturn of the foaming process and decreases of registered temperature inside the foams core. An addition of ROP beneficially influences on foams cellular structure favoring creation of finer cells. Such modification of PUR formulation with ROP increased apparent density, reduced hardness, and resilience of flexible foams. What is more the support factor of FPURFs with ROP was higher in comparison to the reference foam. Along with higher water content in the PUR formulation, apparent density and hardness has decreased and foams ability to absorb energy has been increased. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42372.